2006
DOI: 10.1016/j.jastp.2006.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes of hydrogen-containing species in the stratosphere

Abstract: Understanding the 1% per year increase of stratospheric water vapour from 1954 to 2000 is a great challenge in atmospheric science. The increase is predominantly caused by long-term changes in transport of water vapour into the stratosphere and systematic increases of tropospheric methane levels. This paper gives a review on stratospheric water vapour changes for the 1980 and 2000 time period with emphasis on the contribution of methane oxidation. Predictions for 2050 indicate that likely increases of troposph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Box model calculations by Röckmann et al [2004] indicate that the projected increase of tropospheric methane by WMO scenarios will lead to an increase of the upper stratospheric H 2 O mixing ratio of about 0.4 ppmv by 2050. A similar increase was proposed by Riese et al [2006] as a realistic upper limit of the impact of a H 2 economy.…”
Section: Introductionsupporting
confidence: 64%
“…Box model calculations by Röckmann et al [2004] indicate that the projected increase of tropospheric methane by WMO scenarios will lead to an increase of the upper stratospheric H 2 O mixing ratio of about 0.4 ppmv by 2050. A similar increase was proposed by Riese et al [2006] as a realistic upper limit of the impact of a H 2 economy.…”
Section: Introductionsupporting
confidence: 64%
“…However, we will show that the Harries study used HALOE H 2 O and CH 4 measurements which have biases in the upper stratosphere resulting in an underestimate of H 2 losses in this region. We also note a recent modeling study by Riese et al [2006] which showed that estimated increases of tropospheric H 2 of ∼0.55 ppmv from a possible future hydrogen economy would lead to a 0.3–0.4 ppmv increase in upper stratospheric H 2 O due to increased H 2 oxidation.…”
Section: Introductionmentioning
confidence: 65%
“…2, respectively) of the FPU. The recycle of the anode exhaust gas is not only a valuable recovery of heat, but solves also a base problem of PEM-FC: the release in the atmosphere of molecular hydrogen and steam through the anode exhaust is an environmental risk of not yet well-known impacts on the stratosphere, for the possibility of destruction of ozone, changes in tropospheric chemistry, increase in noctilucent clouds, and stratospheric cooling [92][93][94][95][96].…”
Section: Apus and Models Descriptionmentioning
confidence: 99%